Quality management and fungal transformation in the edible oil industry - Joseph, Manjusha (University of the Free State, 2004)
Approximately 100 000 tonnes of edible frying oil and fat waste, mainly derived from sunflower oil, is produced each year from the estimated 54 000 frying establishments in South Africa. Many of these establishments overuse or abuse their oils to save money. Such practices may result in oil breakdown and the production of harmful compounds, which can cause diseases such as cancer and diarrhoea when consumed. As a result, approximately 30 % of frying oil and fat waste in S.A. can be regarded as unhealthy while the other can be considered still useful for human consumption containing within S.A. regulatory limits i.e. equal to or less than 16 % polymerised triglycerides (PTGs) and/or equal to or less than 25 % polar compounds (PCs). In order to ensure that only oils and fats fit for human consumption are used during frying processes in S.A., it is important that sound quality control procedures are applied to all sectors of the oil industry. This is of special significance when taking into consideration the numerous cases of frying oil misrepresentations, adulteration and overuse reported over the years in S.A. The approximately 70 % of oil wastes still within the regulatory limits have the potential to be processed to safe usable foodstuffs such as Evening Primrose Oil equivalents (EPOeq). Evening Primrose Oil (EPO) has received attention over years as a medicinal supplement due to its high content of gamma-linolenic acid (GLA). A wellknown fact is that the positional distribution of GLA on the glycerol moiety of triacylglycerols has an effect on its functional properties as well as metabolism. When Mucor circinelloides f. circinelloides CBS 108.16 was cultivated on a mixed substrate of sunflower oil (30 g/l) containing 1 %, 5 %, 10 %, 15 % and 45 % (w/w) PTGs and sodium acetate (10 g/l) as carbon sources, most of the oil was utilized after seven days of growth. Marked increases in biomass production as well as in the lipid content of the fungal cells were also noted. Strikingly, these sunflower oils were transformed to fungal oils containing GLA and substantial amounts of linoleic acid (18:2) - also characteristic of evening primrose oil. This phenomenon was however not observed in the medium containing only oils with variable amounts of PTGs (40 g/l) and no acetate. In the presence of acetate, there was an increase in the pH of the medium from pH 5.8 to about neutrality as well as consumption of PTGs from the growth medium whereas in the absence of acetate there was a decrease in the medium pH from pH 5.8 to around pH 3.0 while the relative amounts of PTGs kept increasing in the extracellular lipids. The highest amounts of fungal oils were produced by Mucor circinelloides f. circinelloides using the 5 % and 10 % (w/w) PTG oils. This study suggests the production of EPOeq from sunflower oil waste within regulatory limits using Mucor. Stereospecific analysis of fungal oils obtained from oils with varying PTG concentrations show that the stereospecific positions of some fatty acids (FAs) vary with different PTG concentrations whereas certain FAs are found at the same sn position. The 5 % (w/w) PTG oil yielded a similar FA profile and also a similar sn-distribution profile to that of EPO, however with increasing PTG concentrations of 10 % (w/w), 15 % (w/w) and 45 % (w/w) the FA profiles and the sn-distributions were less similar to that of EPO. Gamma-linolenic acid was found at the sn-2 position in all the oils with varying amounts of PTGs. According to literature, GLA is found preferentially at the sn-2 and sn-3 positions in EPO. Our findings with the positional distribution of EPOeq were similar to that of EPO. Both Nuclear magnetic resonance (NMR) and Gas chromatography (GC) analysis have proved to be extremely valuable tools in the stereospecific analysis of FAs.

Ongeveer 100 000 ton eetbare kookolie- en vetafval, hoofsaaklik afkomstig vanaf sonneblomolie, word elke jaar geproduseer deur ongeveer 54 000 braairestaurante in Suid-Afrika. Baie van hierdie restaurante oorgebruik of misbruik hulle olie om geld te spaar. Sulke praktyke veroorsaak olie-afbraak en die produksie van skadelik verbindings wat siektes soos kanker en diaree kan veroorsaak as dit ingeneem word. Dus kan ongeveer 30 % van kookolie- en vetafval in S.A. beskou word as skadelik terwyl die res gesien kan word as bruikbaar vir menslike gebruik aangesien dit steeds binne die S.A. regulatoriese limiete val, d.i. gelyk aan of minder as 16 % gepolimeriseerde trigliseriede (PTGs) en/of gelyk aan of minder as 25 % polêre komponente (PKs). Om te verseker dat slegs olies en vette wat geskik is vir menslike gebruik in braaiprosesse in S.A. gebruik word, is dit belangrik dat goeie kwaliteitsbeheerprosedures in alle afdelings van die olieindustrie toegepas word. Dit is veral belangrik as die verskeie gevalle van kookoliewanvoorstelling, -vermenging en oorgebruik wat oor die jare in S.A. gerapporteer is, inaggeneem word. Die ongeveer 70 % olie-afval wat steeds binne limiete is, het die potensiaal om na veilige, bruikbare voedingstowwe soos Aandblomolieekwivalente (AOekw) verwerk te word. Aandblomolie (AO) het oor die jare baie aandag geniet as ‘n mediese aanvulling as gevolg van ‘n hoë gamma-linoleensuur (GLS) inhoud. Dis bekend dat die posisionele verspreiding van GLS op die gliseroleenheid van triasielgliserole ‘n effek het op die funksionele eienskappe en metabolisme. Mucor circinelloides f. circinelloides CBS 108.16 is gekweek in gemengde media met sonneblomolie (30g/l) wat 1 %, 5 %, 10 %, 15 % of 45 % (m/m) PTGs bevat het, asook natriumasetaat (10g/l) as koolstofbronne. Meeste van die olie is gebruik na sewe dae van groei. Merkbare toenames in biomassaproduksie asook lipiedinhoud van fungiselle is opgemerk. Die sonneblomolies is getransformeer na fungi-olies met GLS en merkbare hoeveelhede linoleiënsuur (18:2) - ook kenmerkend van AO. Hierdie verskynsel is egter nie waargeneem in die medium wat slegs olie met verskillende hoeveelhede PTGs (40 g/l) bevat het en geen asetaat nie. In die teenwoordigheid van asetaat, is ‘n toename in die pH van die medium, vanaf pH 5.8 na ongeveer neutraal, asook ‘n verbruik van PTGs uit die groeimedium waargeneem. In die afwesigheid van asetaat was daar egter ‘n afname in die medium se pH, vanaf pH 5.8 na pH 3.0, terwyl die relatiewe hoeveelhede PTGs in die ekstrasellulêre lipiede toegeneem het. Die grootste hoeveelheid fungi-olie is geproduseer deur Mucor circinelloides f. circinelloides op 5 % en 10 % (m/m) PTGbevattende olies. Die studie dui daarop dat die produksie van AOekw vanaf sonneblomolieafval binne regulatoriese limiete deur Mucor moontlik is. Stereospesifieke analises van fungi-olie, verkry vanaf olie met verskillende PTG-konsentrasies toon aan dat die stereospesifieke posisies van sommige vetsure (VSe) variëer met verskilende PTG-konsentrasies, terwyl ander VSe in dieselfde sn-posisie aangetref word. Die 5 % (m/m) PTG-olie het ‘n soortgelyke vetsuurprofiel en sn-verspreiding gelewer as AO. Met toenemende PTG-konsentrasies van 10 % (m/m), 15 % (m/m) en 45 % (m/m) het die vetsuurprofiele en sn-verspreiding egter minder ooreenstemming getoon met AO. Gamma-linoleensuur is in die sn-2 posisie gevind in alle olies met verskillende hoeveelhede PTGs. Volgens literatuur word GLS meestal in die sn-2 en sn-3 posisies in AO aangetref. Ons bevindinge aangaande die sn-verspreiding van AOekw is soortgelyke aan die van AO. Beide kernmagnetiese resonansie (KMR) en gaschromatografie (GC) analises was waardevolle in die stereospesifieke analises.
Thesis (Ph.D. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2004
Keywords: Gamma-linolenic acid; Malpractices; Mucor circinelloides f. circinelloides; Oil waste; Polymerised triglycerides; Stereospecific analysis; Sodium acetate; Evening primrose oil; Evening primrose oil equivalents; Nuclear magnetic resonance; Oils and fats, Edible; Food adulteration and inspection; Food industry and trade -- Quality control